2015
DOI: 10.1111/trf.13053
|View full text |Cite
|
Sign up to set email alerts
|

A multicenter study on the performance of a fully automated, walk‐away high‐throughput analyzer for pretransfusion testing in the US population

Abstract: Grifols' Erytra analyzer showed reliable efficacy compared with equivalent FDA-licensed reagents and FDA-cleared instruments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
17
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 23 publications
(20 reference statements)
3
17
1
Order By: Relevance
“…As in Chang et al [8], Cid et al [13] and Garozzo et al [11], the most frequently identified antibodies were anti-D (24.1%), in direct relationship with antenatal prophylaxis against haemolytic disease of the newborn, and anti-E (16.7%). Anti-K represented only 7.4% in our study while a greater percentage was described in Roback et al [9] and Tayler et al [10]. The concordance rate between Bio-Rad and Grifols is 100%, between Bio-Rad and OCD 91%, between OCD and Grifols 87% and between all three methods 91%.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…As in Chang et al [8], Cid et al [13] and Garozzo et al [11], the most frequently identified antibodies were anti-D (24.1%), in direct relationship with antenatal prophylaxis against haemolytic disease of the newborn, and anti-E (16.7%). Anti-K represented only 7.4% in our study while a greater percentage was described in Roback et al [9] and Tayler et al [10]. The concordance rate between Bio-Rad and Grifols is 100%, between Bio-Rad and OCD 91%, between OCD and Grifols 87% and between all three methods 91%.…”
Section: Discussioncontrasting
confidence: 49%
“…However, only few studies have focused on differences in identification of those RBC alloantibodies. Chang et al [8], Roback et al [9] and Taylor et al [10] compared test cell panels form Bio-Rad and Grifols for RBC antibody identification. Garozzo et al [11] compared results with test cell panels from OCD with those from Immucor.…”
Section: Introductionmentioning
confidence: 99%
“…Following this, 50 l 1% RBCs was added to microtubes and centrifuged for 9 min using a preset cycle for antibody identification. The results of reactions were generated automatically through artificial vision technology and evaluated using a scale of strength as follows: negative (-) or increasingly positive at 1ϩ, 2ϩ, 3ϩ, or 4ϩ (20,57). The experiment was performed under the supervision of trained and experienced medical technicians.…”
Section: Methodsmentioning
confidence: 99%
“…As the scalable evolution of the Erytra® blood typing analyser (Chang et al ., ; Roback et al ., ), the new Erytra Eflexis® (Grifols) is a fully automated, benchtop, compact analyser for pre‐transfusion compatibility testing using the 8‐column DG Gel® card technology (Taylor et al ., ).…”
mentioning
confidence: 99%